Cyclic production of biocompatible few-layer graphene ink with in-line shear-mixing for inkjet-printed electrodes and Li-ion energy storage - Coleman, Jonathan; Carey, Tian (My University, 2022)
The scalable production of two-dimensional (2D) materials is needed to accelerate their adoption to industry. In this work, we present a low-cost in-line and enclosed process of exfoliation based on high-shear mixing to create aqueous dispersions of few-layer graphene, on a large scale with a Yw ~ 100% yield by weight and throughput of φ ~ 8.3 g h−1. The in-line process minimises basal plane defects compared to traditional beaker-based shear mixing which we attribute to a reduced Reynolds number, Re ~ 105. We demonstrate highly conductive graphene material with conductivities as high as σ ∼ 1.5 × 104 S m−1 leading to sheet- resistances as low as Rs ∼ 2.6 Ω □−1 (t ∼ 25 μm). The process is ideal for formulating non-toxic, biocompatible and highly concentrated (c ∼ 100 mg ml−1) inks. We utilise the graphene inks for inkjet printable conductive interconnects and lithium-ion battery anode composites that demonstrate a low-rate lithium storage capability of 370 mAh g−1, close to the theoretical capacity of graphite. Finally, we demonstrate the biocompatibility of the graphene inks with human colon cells and human umbilical vein endothelial cells at high c ∼ 1 mg ml−1 facilitating a route for the use of the graphene inks in applications that require biocompatibility at high c such as electronic textiles.
PUBLISHED
cited By 0
Keywords: two-dimensional (2D) materials; high-shear mixing; electronic textiles